2015
DOI: 10.1007/s00210-015-1115-4
|View full text |Cite
|
Sign up to set email alerts
|

Organ-protective effects on the liver and kidney by minocycline in small piglets undergoing cardiopulonary bypass

Abstract: Cardiopulmonary bypass (CPB) often is required for the operative correction of congenital heart defects in small infants. Unfortunately, CPB is associated with injury of inner organs such as the brain, kidney, lung, and liver. Renal failure and increase in liver enzymes are typical side effects observed after CPB. Here, we investigate whether organ protection of the kidney and liver can be achieved with the application of minocycline, which is known-besides its anti-infective effects-to act as a poly-ADP-ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…The same effect could be shown in liver, where minocycline significantly decreased hepatic TNFα and IL-1β expression and improved liver function (Li et al, 2015 ). The PARP-inhibitory effect of minocycline and its positive influence on cell apoptosis were also revealed in other studies and by our working group: piglets subjected to cardio-pulmonary bypass showed less organ dysfunction (hippocampus, liver, kidney) when minocycline was administered before bypass and during reperfusion (Tao et al, 2010 ; Dhein et al, 2015 ; Salameh et al, 2015 ).…”
Section: Introductionsupporting
confidence: 65%
“…The same effect could be shown in liver, where minocycline significantly decreased hepatic TNFα and IL-1β expression and improved liver function (Li et al, 2015 ). The PARP-inhibitory effect of minocycline and its positive influence on cell apoptosis were also revealed in other studies and by our working group: piglets subjected to cardio-pulmonary bypass showed less organ dysfunction (hippocampus, liver, kidney) when minocycline was administered before bypass and during reperfusion (Tao et al, 2010 ; Dhein et al, 2015 ; Salameh et al, 2015 ).…”
Section: Introductionsupporting
confidence: 65%
“…Specifically, AIF was significantly inhibited by minocycline in left ventricular endocardium. Similar effects of minocycline have been described for hippocampus tissue in a mouse model of experimental epilepsy and by the authors in a study on liver and kidneys of piglets undergoing cardio‐pulmonary bypass …”
Section: Discussionsupporting
confidence: 74%
“…Other studies have concluded that minocycline has positive effects on liver and kidney function during cardio-pulmonary bypass while in a model of myocardial infarction in diabetic rats this drug reduced infarct size in diabetic rats. 26,27 These results also suggest that under the stress of ischemia and reperfusion minocycline is able to protect vulnerable tissues.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Extracorporeal circulation can cause damage to the internal organs, such as brain, kidney, lung, and liver. Dhein et al [ 42 ] revealed that extracorporeal circulation decreased the ATP content in kidney and liver, but minocycline could significantly increase the ATP level in organs and reduce the injuries of kidney and liver. The Na + –K + -ATPase, a kind of protease, is located in the membranes of the cells and organelles functioning in substance transport, energy conversion, information transmission, cell membrane integrity maintenance and tissue metabolism.…”
Section: Discussionmentioning
confidence: 99%